2020
DOI: 10.3866/pku.whxb202001004
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Insight into Changes in the Vibrational Spectrum of Ionic Liquids under External Electric Field

Abstract: Vibrational spectroscopy is a powerful tool for studying the microstructure of liquids, and anatomizing the nature of the vibrational spectrum (VS) is promising for investigating changes in the properties of liquid structures under external conditions. In this study, molecular dynamics (MD) simulations have been performed to explore changes in the VS of 1-ethyl-3-methylimidazolium hexafluorophosphate ([Emim][PF6]) ionic liquid (IL) under an external electric field (EEF) ranging from 0 to 10 V•nm −1 at 350 K. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Specifically, cocatalysts can be acted as electron carriers to accept electrons from photogenerated g-C 3 N 4 to their Fermi level, which inhibit the recombination of e − -h + pairs, and then provide abundant active sites to react with absorbed substance (Figure 8A). [25,131,132] Excitingly, some studies have shown that these QDs/g-C 3 N 4 might be a promising alternative to noble metal and avoid high cost. [42,69,97] For instance, Zeng et al adopted a facile strategy to synthesize CoP QDs/ultrafine g-C 3 N 4 fiber (CoP QDs/CNF) photocatalysts.…”
Section: As Cocatalystmentioning
confidence: 99%
See 3 more Smart Citations
“…Specifically, cocatalysts can be acted as electron carriers to accept electrons from photogenerated g-C 3 N 4 to their Fermi level, which inhibit the recombination of e − -h + pairs, and then provide abundant active sites to react with absorbed substance (Figure 8A). [25,131,132] Excitingly, some studies have shown that these QDs/g-C 3 N 4 might be a promising alternative to noble metal and avoid high cost. [42,69,97] For instance, Zeng et al adopted a facile strategy to synthesize CoP QDs/ultrafine g-C 3 N 4 fiber (CoP QDs/CNF) photocatalysts.…”
Section: As Cocatalystmentioning
confidence: 99%
“…[43] The similar transition metal phosphates (like Ni 2 P) in composites with g-C 3 N 4 , efficiently inhibited the recombination of photogenerated e − -h + pairs, which endowed an excellent photocatalytic performance without noble metals. [25,42,52,69] Apart from CQDs or GQDs considered as cocatalysts to enhance charge transfer ability, researchers have taken advantage of their up-conversion properties, which stimulated composites to form more e − -h + pairs. [100,119,120] Recently, a breakthrough study has found that the more uniform and ordered combination of QDs and g-C 3 N 4 endowed better photocatalysis of the composite.…”
Section: H 2 Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…A promising solution for reducing growing CO2 levels while enhancing energy production is using visible light-driven water splitting for hydrogen generation [1][2][3][4]. Until now, a large number of molecules and inorganic, organic, and heterojunc-tion semiconductor photocatalytic systems have been designed for realizing photocatalytic hydrogen evolution [5][6][7][8][9][10][11][12][13][14][15][16][17]. For photocatalytic H2 evolution (PHE), covalent organic frameworks (COFs) with a large surface area, high crystallinity, and a distinct structure are considered viable alternatives to inorganic semiconductor photocatalysts [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%